Filmes finos de compostos semicondutores: preparação de CdS e da junção Cu2-XSe/MEH-PPV - Rabelo, Adriano César (2008)
In this work thin films of semiconductor compounds were prepared. Focus was on a recipe for preparation of cadmium sulphide onto copper selenide substrate. Copper selenide thin films dissolve when in contact with the chemical bath for deposition cadmium sulphide. This drawback triggered an investigation for using milder chelating agents. A new bath composition was determined from chemical equilibrium analysis of about ten species supposedly present in the bath, mass balance and charge balance. From the results, a thin film of. cadmium sulphide has been prepared on glass substrate by chemical bath deposition using sodium acetate, sodium hydroxide and thiourea. Absorption spectra of the film in the visible range was registered and compared with the spectra from others authors. The band gap of the film was estimated from the spectra. The junction copper selenide and poly-2-methoxy-5- (2 -ethylhexyloxy)-phenylenevinilene was prepared and characterized. Copper selenide was prepared on copper by chemical bath deposition using sodium selenosulphate. The polymeric film was prepared by casting technique, in which the polymer is dissolved in tetrahidrofurane, dropped onto the substrate and let to dry. Ohmic contact was prepared using graphite conductive glue. This glue was developed for this purpose and is made up from graphite powder, epoxy and polimercaptan dissolved in tetrahidrofurano. The electrical properties of the junction were determined from current-potential curves. By using the Fowler-Nordheim model, the energy barrier height was calculated. The results were compared with the literature results obtained with a similar devices, namely ITO/MEH-PPV. The energy barrier height of copper selenide/MEH-PPV is about thirty times smaller than the energy barrier height of ITO/MEH-PPV. The conclusion is that copper selenide is a promising material for use in photoluminescent diodes.